Development of Discovery Learning-Based Teaching Materials to Improve Students' Critical Thinking Abilities in the Kurikulum Merdeka in Class V of Elementary Schools - Yuris Nasri; Rifma; Muhammadi; Salmaini (Postgraduate, University of Mataram, 2024)
This research was motivated by findings from initial identification through interviews and observations at SDN 18 V Koto Timur, which revealed that fifth grade students faced difficulties in science and technology subjects, especially regarding low enthusiasm and active participation in learning. The type of research used is Research and Development with the ADDIE development model. In this development research, the research subjects were 30 class V students and the research object was the development of DL-based teaching materials to improve students' critical thinking skills. Data collection techniques use validation sheets, practicality questionnaires and learning outcomes tests. Based on the results of the development research carried out, the validity results of the Merdeka Curriculum teaching module obtained an average of 89% (very valid), the material expert validator obtained a result of 90.6% (very valid), the results for the language expert were 93.3% (very valid). ), and media expert acquisition was 85.4% (valid). The practicality of the module was tested through individual trials on 8 students at SDN 18 V Koto Timur and 8 students at SDN 01 V Koto Timur resulting in an average total score of 88.96% and 86.46%, which was categorized as